Pelaksanaan Perceraian Dengan Alasan Suami Mafkud: (Studi di Pengadilan Agama Selong) - Rahmianti Rahmianti; Lalu Hadi Adha (Private Law, 2023)
The purpose of this study was to determine the legal arrangements for divorce because husbands are mafkud in the compilation of Islamic law (KHI) and Law no. 1 of 1974 concerning Marriage, and the obstacles for judges in deciding divorce because the husband is willing to attend the Selong Religious Court. The research method used is empirical normative legal research. From the results of the study, it was analyzed that the legal arrangement because the husband is mafkud can be seen in the provisions of Article 116 part one and Article 116 letter (g). Islamic Law Compilation. In addition, Article 39 Paragraph 2 of Law Number 1 of 1974 concerning Marriage and Article 19 of Government Regulation Number 9 of 1975 Article 19 of Government Regulation Number 9 of 1975 can be used as the basis for a wife to file for divorce from her mafqud husband. The obstacles for judges in deciding divorce because Mafkud's husband at the Selong Religious Court is divided into two factors, namely internal factors and external factors. The internal factors include factors of law and factors of facilities and infrastructure. Then external factors caused by the parties and descriptions of sanctions that sometimes change.